KAJIAN PROSES HIDROLISIS ENZIMATIK PATI DALAM TEPUNG SORGUM MANIS [Study of Enzymatic Hydrolysis of Sweet Sorghum Strach] - Triwiyono, Bambang; supriyanto, Supriyanto; Setiadi, Sigit; Sabirin, Sabirin (Jurnal Teknologi & Industri Hasil Pertanian, 1997)
Sweet Sorghum strach (Sorghum bicolor, L. Moench) was hydrolyzed for substituing the molasses on fermentation industry, i.e. ethanol and glutamic acid production. Pretreatment for strach conversion of the different stored strach by means of athmospheric batch cooking process presented the contradictive result. The amylases dosage for strach conversio of the stored sweet sorghum seem to be equal to the fresh cassava processing. Both total sugar (20 to 28% w/v) and te screened meal size (20-100 mesh) had a litlle effect on the rate of strach hydrolysis. After 24 hours of incubation, the strach was converted to the reducing sugar up to 85% dextrose equivalent. On the contrary, strach of fresh seet sorghum could not be liquified as the concentration of total sugar was reduced to 15% (w/v). The matrix protei of glutelin in which this protein bids the strach granules contributes to the diffficulty of digesting sweet sorgum meal.